Preparation method of medical equiaxial ultra-fine grain titanium-zirconium alloy rod wire

In the preparation of medical isometric ultrafine crystal titanium-zirconium alloy rod wire materials, vacuum consumable arc furnace smelting, forging, quenching, hot rolling, cold rolling and severe plastic deformation processes such as sponge titanium and sponge zirconium are used, The problems of low efficiency of traditional methods and uneven material properties were solved, and isometric ultrafine crystal titanium-zirconium alloy rod wire material with high strength and good wear resistance were prepared to meet the needs of dental medical devices.

CN119114670AActive Publication Date: 2024-12-13SHENZHEN NATAI MEDICAL TECH CO LTD

Patent Information

Application Number
CN202411135996.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-13
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

It is difficult to prepare medical isometric ultrafine crystal titanium-zirconium alloy rod wire materials for high strength and wear resistance. The traditional thermal machining method is low in efficiency and the material structure performance is uneven.

Method used

Use sponge titanium, sponge zirconium and zirconium dioxide to prepare ingredients in preset proportions, and melted into ingots through a vacuum consumable arc furnace, forging, quenching, hot rolling, cold rolling, recrystallization annealing and violent plastic deformation processing, combined with pulling Extraction and straightening treatment, and finally surface treatment is carried out to prepare isometric ultrafine crystal titanium-zirconium alloy rod wire.

Benefits of technology

Mass production of isometric ultrafine crystal titanium-zirconium alloy rod wire materials with a diameter of 1mm-8mm and a length of more than 600mm has been achieved, with high strength and high fatigue strength to meet the material needs of dental medical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114670A_ABST
    Figure CN119114670A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a medical titanium-zirconium alloy bar wire. The preparation method comprises the processes of ingot casting, forging, quenching, hot rolling, quenching, cold rolling, recrystallization annealing, severe plastic deformation, drawing, straightening, annealing and surface treatment. The microstructure of the alloy is regulated and controlled by introducing high-density defects into the material through severe plastic deformation and combining quenching heat treatment, preparation of the titanium-zirconium alloy with high strength and plasticity and good fracture toughness is achieved, and equiaxial ultra-fine grain titanium-zirconium alloy bars and wires with the diameter ranging from 1 mm to 8 mm and the length larger than 600 mm can be produced in batches. High strength and high fatigue strength can be obtained, and the requirements of dental medical instruments for raw materials are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomaterial preparation, and more specifically to a method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire. Background Art

[0002] In dental medical devices, the most widely used metal materials are pure titanium and Ti-6Al-4V, but pure titanium is not strong enough, Ti-6Al-4V has a high elastic modulus and the V element is toxic. Titanium-zirconium alloy has a low elastic modulus, excellent mechanical properties, good corrosion resistance and biocompatibility, and has become a new type of raw material for dental devices.

[0003] The industry currently uses traditional thermal mechanical processing methods to produce Φ1mm-8mm cylindrical Ti-15Zr titanium alloy rods and wires. However, the raw materials of these Ti-15Zr rods and wires are not ultrafine-grained materials. Therefore, they have key problems such as low strength and poor wear resistance, which do not meet the needs of medical devices.

[0004] Continuous equal channel angular extrusion technology combines equal channel angular extrusion and continuous extrusion processes to achieve the preparation of large-sized ultrafine-grained materials. Although large-sized ultrafine-grained Ti-15Zr alloy rods and wires can be produced, the accumulated strain in a single processing process is small, and large deformation often requires many processing times and repeated extrusion, resulting in low processing efficiency. In addition, the ultrafine grains are not equiaxed crystals, and there are problems such as uneven deformation of the formed material and poor uniformity of the organizational properties of the resulting material products.

[0005] Therefore, there is an urgent need to provide a method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rods and wires that can prepare large-sized equiaxed ultrafine-grained titanium-zirconium alloy rods and wires. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rods and wires.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire, characterized by comprising:

[0009] S1. Mix titanium sponge, zirconium sponge and zirconium dioxide according to a preset ratio and melt them into ingots;

[0010] S2. After the ingot is kept at 850°C-1000°C, it is forged to obtain a forged billet;

[0011] S3. The forging blank is subjected to a first quenching treatment;

[0012] S4. The forging blank is kept at 770°C-840°C and then rolled to obtain a rolled strip;

[0013] S5. The rolled strip is subjected to a second quenching treatment;

[0014] S6. rolling the rolled strip at room temperature to obtain an ultrafine grained rod blank;

[0015] S7. Recrystallization annealing treatment is performed on the ultrafine grained rod blank;

[0016] S8. The ultrafine crystal rod blank is subjected to severe plastic deformation processing to obtain an equiaxed ultrafine crystal rod blank;

[0017] S9. Drawing and reducing the equiaxed ultrafine grained rod blank at room temperature to obtain a rod wire;

[0018] S10. Straightening the rod wire;

[0019] S11. Annealing the rod wire;

[0020] S12. Surface treatment is performed on the rods and wires to obtain qualified rods and wires.

[0021] Implementing the embodiments of the present invention will have the following beneficial effects:

[0022] The embodiment of the present invention discloses a method for preparing equiaxed ultrafine-grained medical titanium-zirconium alloy rods and wires, including ingot casting, forging, quenching, hot rolling, quenching, cold rolling, recrystallization annealing, severe plastic deformation, drawing, straightening, annealing and surface treatment processes. The microstructure of the alloy is regulated by introducing high-density defects inside the material through severe plastic deformation combined with quenching heat treatment to achieve the preparation of titanium-zirconium alloy with high strength plasticity and good fracture toughness, and can realize batch production of equiaxed ultrafine-grained titanium-zirconium alloy rods and wires with a diameter between 1mm-8mm and a length greater than 600mm, which can obtain high strength and high fatigue strength to meet the demand for raw materials for dental medical devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] in:

[0025] Figure 1 The present invention provides a flow chart of a method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rods and wires.

[0026] Figure 2 It is a schematic diagram of the severe plastic deformation die provided by the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Reference Figure 1 The present invention discloses a method for preparing a medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire, comprising:

[0029] S1. Titanium sponge, zirconium sponge and zirconium dioxide are mixed in a preset ratio and melted into an ingot in a vacuum consumable arc furnace;

[0030] S2. After the ingot is kept at 850°C-1000°C, it is forged to obtain a forged billet;

[0031] S3. Performing a first quenching treatment on the forging blank;

[0032] S4. The forging blank is kept at 770°C-840°C and then rolled to obtain a rolled strip;

[0033] S5. The rolled strip is subjected to a second quenching treatment;

[0034] S6. rolling the strip at room temperature to obtain an ultrafine grained rod blank;

[0035] S7. Recrystallization annealing treatment is performed on the ultrafine grained rod blank;

[0036] S8. The ultrafine grained ingot is subjected to severe plastic deformation to obtain an equiaxed ultrafine grained ingot;

[0037] S9. Drawing and reducing the equiaxed ultrafine grained rod blank at room temperature to obtain a rod wire;

[0038] S10. Use a straightening device to straighten the rod and wire;

[0039] S11. Annealing the rod and wire;

[0040] S12. Surface treatment is performed on the rods and wires to obtain qualified rods and wires.

[0041] It should be noted that the titanium-zirconium alloy rod and wire prepared in this embodiment includes the following components in mass percentage: Zr: 14-16.5%, the balance is Ti and inevitable impurities. The inevitable impurities are impurities in the added sponge zirconium and sponge titanium, wherein: 0<C≤0.10%, 0<O≤0.20%, 0<N≤0.05%, 0<H≤0.08%, 0<Fe≤0.25%.

[0042] Specifically, in step S1, titanium sponge, zirconium sponge, ZrO 2 The powder is mixed according to the preset ratio; it is smelted 3-4 times in a vacuum consumable arc furnace with a vacuum degree of 10 -1 Pa-10 -3 Pa, working current 1kA-10kA, working voltage 10V-50V, to obtain titanium-zirconium alloy ingot.

[0043] In step S2, the ingot is kept in the β phase temperature zone (850°C-1000°C) of the titanium-zirconium alloy for 1h-5h, air-cooled, and free forged by a fast forging machine, with the deformation amount of each fire being not less than 50%, to obtain a forged billet.

[0044] In step S3, the forging blank is subjected to a first quenching treatment, which specifically includes: the forging blank obtained by forging is kept in the β phase temperature range of the titanium-zirconium alloy for 1h-3h, and then quickly cooled with water or liquid nitrogen.

[0045] The ingot is kept in the β phase and then cooled rapidly, and the microstructure forms dispersed α' needle-shaped martensite.

[0046] In step S4, the forging blank is kept in the α+β phase temperature range (770°C-840°C) of the titanium-zirconium alloy for 1-3 hours, and then rolled by a horizontal rolling mill with a single-pass deformation rate of less than 15% to obtain a rolled strip.

[0047] The forging billet is hot rolled after being kept in the α+β phase temperature zone. The martensite structure inside the material is deformed, and the dislocations are rearranged to form a new fine submicron grain structure, which can effectively improve the strength of the material.

[0048] In step S5, the rolled strip is subjected to a second quenching treatment, which specifically includes: the rolled strip obtained by rolling after being kept in the α+β phase temperature range of the titanium-zirconium alloy for 1h-3h is rapidly cooled with water or liquid nitrogen.

[0049] The rolled strip is rapidly cooled after being kept in the α+β phase region to form an α+α' structure. The soft and tough α phase provides excellent elongation, so that subsequent room temperature rolling will not crack.

[0050] In step S6, a cold rolling mill is used to roll the strip at room temperature, and the deformation of a single pass is less than 15% and the total deformation is greater than 50%.

[0051] Cold rolling at room temperature can further fully break the grains inside the rolled strip to obtain an ultrafine crystal rod blank, and the ultrafine crystal rod blank at this time is a non-equiaxed ultrafine crystal rod blank.

[0052] The recrystallization annealing in step S7 includes heat preservation of the ultrafine crystal ingot at 600-700°C for 0.5-3 hours and then air cooling. The recrystallization annealing eliminates the work hardening phenomenon in the material after cold deformation, and restores and improves the plasticity and toughness of the material.

[0053] In step S8, a severe plastic deformation method is used to prepare an equiaxed ultrafine-grained alloy rod blank, and the severe plastic deformation method includes high-pressure torsion, equal-diameter angular extrusion, multi-directional forging and other technologies.

[0054] Optionally, in step S8, the rod blank is cut to a fixed length, and then subjected to equal-diameter angular extrusion processing. The die diagram is as follows: Figure 2 , the turning angle α is 120°. Molybdenum disulfide is used as a lubricant, and the equal-diameter angular extrusion processing speed is between 1mm / s-10mm / s. Each time the rod billet passes through the die is a pass, and the sample rotates 90° clockwise between each pass. The processing temperature is between 400℃-500℃, and the processing passes are between 4-8 passes.

[0055] Optionally, the diameter of the die for processing the original rod by equal-diameter angular extrusion includes but is not limited to 8mm-20mm, and the die can process rods between 2mm and 20mm. The turning radius of the die includes but is not limited to 120°, and the turning radius can be between 90° and 160°.

[0056] In step S9, a roller mill drawing device is used to perform multiple passes of room temperature drawing, and the deformation of a single pass is between 10% and 15%. Subsequently, stress relief annealing is performed, and rods and wires are obtained after multiple passes of drawing.

[0057] Through the cycle of room temperature drawing and stress relief annealing, the equiaxed ultrafine-grained alloy rod billet is further reduced to obtain rods and wires with a length greater than 1m and specifications close to the requirements of the finished product.

[0058] In step S10, the rod wire is first cut into a required length, and then straightened by a straightening device to control the straightness to be ≤1 mm / m.

[0059] In step S11, an annealing furnace is used to anneal the rods and wires at a temperature of 450° C. to 650° C. for a time of 20 min to 90 min.

[0060] In step S12, a centerless grinder, pickling polishing or plasma polishing surface treatment equipment is used to perform surface treatment on the rod and wire to remove the oxide scale on the surface of the rod and wire. The surface roughness of the qualified rod and wire is less than or equal to 0.8 μm. An ultrafine-grained titanium-zirconium alloy rod and wire with a bright surface, annealed state and excellent straightness is obtained.

[0061] It can be understood that, on the one hand, the preparation method of the medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire provided by the present invention can produce medical ultrafine-grained titanium-zirconium alloy rod and wire of various specifications, providing qualified raw materials for dental medical devices. On the other hand, the present invention improves the strength of titanium by adding titanium-zirconium elements that are harmless to the human body, meets the strength and wear resistance required by the implant, and at the same time, eliminates the risk of human damage caused by the precipitation of harmful elements, and meets the requirements of medical devices for raw material performance. On the other hand, the present invention adopts a special processing technology, through a method combining strong deformation and heat treatment, that is, through severe plastic deformation, high-density defects (dislocations, etc.) are introduced into the material, combined with quenching heat treatment to regulate the microstructure of the alloy, to achieve the preparation of titanium-zirconium alloy with high strength plasticity and good fracture toughness, and can realize batch production of equiaxed ultrafine-grained titanium-zirconium alloy rods and wires with a diameter between 1mm-8mm and a length greater than 600mm, which can obtain high strength and high fatigue strength, and meet the demand for raw materials for dental medical devices.

[0062] Example 1

[0063] The titanium-zirconium alloy rod and wire in this embodiment includes, by mass percentage, Zr: 15.15%, C: 0.004%, O: 0.193%, N: 0.018%, H: 0.008%, Fe: 0.028%, and the remainder is Ti.

[0064] The method for preparing the titanium-zirconium alloy rod and wire in this embodiment comprises:

[0065] Step 1: Use titanium sponge, zirconium sponge, ZrO 2 The powder was divided into titanium-zirconium alloy components and smelted four times by vacuum self-consumption. The vacuum degree of the first smelting was 5×10 -3 Pa, working current 5.5kA, working voltage 30V; the vacuum degree of the second melting is 10 -2 Pa, working current 5.5kA, working voltage 30V; the third melting vacuum degree is 10 -1 Pa, working current 8.0kA, working voltage 30V; the fourth smelting vacuum degree is 10 -1 Pa, working current 7.5kA, working voltage 30V; obtain Φ260mmTi-Zr alloy ingot.

[0066] Step 2: After keeping the ingot at 900°C for 2 hours, free forging is performed using a fast forging machine, and the deformation amount of each fire is controlled at 60% to obtain a Φ120mm forging billet.

[0067] Step 3: Keep the forging blank at 900°C for 1.5 hours and then quickly water cool it for quenching.

[0068] Step 4: After keeping the forging billet at 800° C. for 1.5 h, the forging billet is rolled using a Y-type three-roller continuous rolling mill, with the deformation amount of each pass controlled at 13% to obtain a Φ12 mm rolled bar.

[0069] Step 5: Keep the rolled strip at 780°C for 1 hour and then quickly water cool it for quenching.

[0070] Step 6: Use a cold rolling device to continuously cold roll the rolled strip, with a single-pass deformation of 10%. After the deformation reaches 40%-45%, intermediate annealing is performed at 650°C and 1h. After multiple cycles, a Φ6mm ultrafine grain rod blank is obtained.

[0071] Step 7: Keep the rod blank at 700°C for 0.5h and then air-cool it for recrystallization annealing heat treatment.

[0072] Step 8: Cut the rod into 500mm length, cut and cut, and perform equal-diameter angular extrusion to obtain equiaxed ultrafine-grained alloy rods. The processing temperature is 400℃, the turning angle is 120°, molybdenum disulfide is used as a lubricant, the processing speed is between 5mm / s, and the rod rotates 90° clockwise after passing through the die each time, and the processing passes are 6 times.

[0073] Step nine, cold drawing the equiaxed ultrafine grain alloy rod blank at room temperature with a drawing device, a single-pass deformation of 11-13%, lubrication with lubricating fluid, intermediate annealing at 650°C for 1h, and then cold drawing again, after multiple cycles, Φ4mm rod wire is obtained.

[0074] Step 10: Cut the rods and wires into 1000mm lengths each, and use a slider straightening machine to straighten the rods and wires. After straightening, the straightness is 0.3mm / m.

[0075] Step 11: anneal the rods and wires at 600°C for 40 minutes.

[0076] Step 12: Use a centerless grinder to remove the surface oxide layer of the annealed rod and wire, and use wet polishing to polish the rod and wire surface to a roughness of 0.4 μm.

[0077] Table 1 is the mechanical properties test results of the Φ4.0 mm titanium-zirconium alloy rod and wire obtained in Example 1

[0078]

[0079] Example 2

[0080] The titanium-zirconium alloy rod and wire in this embodiment includes, by mass percentage, Zr: 15.60%, C: 0.008%, O: 0.189%, N: 0.009%, H: 0.005%, Fe: 0.022%, and the remainder is Ti.

[0081] The method for preparing the titanium-zirconium alloy rod and wire in this embodiment comprises:

[0082] Step 1: Use titanium sponge, zirconium sponge, ZrO 2 The powder is divided into titanium zirconium alloy components and smelted three times by vacuum consumable method. The vacuum degree of the first smelting is 4×10 -3 Pa, working current 5.5kA, working voltage 30V; the vacuum degree of the second melting is 10 -2 Pa, working current 5.5kA, working voltage 30V; the third melting vacuum degree is 10 -1 Pa, working current 8.0kA, working voltage 30V; obtain Φ280mmTi-Zr alloy ingot.

[0083] Step 2: After keeping the ingot at 900°C for 2 hours, free forging is performed using a fast forging machine, and the deformation amount of each fire is controlled at 65% to obtain a Φ140mm forging billet.

[0084] Step 3: Keep the forging blank at 900°C for 1.5 hours and then quickly water cool it for quenching.

[0085] Step 4: After keeping the forging billet at 780° C. for 1.5 h, the forging billet is rolled using a Y-type three-roller continuous rolling mill, with the deformation amount of each pass controlled at 12% to obtain a Φ10 mm rolled bar.

[0086] Step 5: Keep the rolled strip at 780°C for 1 hour and then quickly water cool it for quenching.

[0087] Step 6: Use a cold rolling device to continuously cold roll the rolled strip, with a single-pass deformation of 12%. After the deformation reaches 40%-45%, intermediate annealing is performed at 650°C and 1h. After multiple cycles, a Φ6mm ultrafine grain rod blank is obtained.

[0088] Step 7: Keep the rod blank at 680°C for 0.5h and then air-cool it for recrystallization annealing heat treatment.

[0089] Step 8: Cut the rod blank to 500 mm in length, cut it, and perform equal-diameter angular extrusion to obtain an equiaxed ultrafine-grained rod blank. The processing temperature is 450°C, the turning angle is 120°, molybdenum disulfide is used as a lubricant, the processing speed is between 5 mm / s, and the rod blank rotates 90° clockwise after passing through the die each time, and the processing number is 6.

[0090] Step nine: cold-draw the equiaxed ultrafine crystal rod blank with a drawing device, with a single-pass deformation of 10-12%. Lubrication is performed with lubricating fluid, intermediate annealing is performed at 600° C. for 1 hour, and then cold-drawing is performed again. After multiple cycles, Φ5 mm rod wire is obtained.

[0091] Step 10: Cut the rods and wires into 1000mm lengths each, and use a slider straightening machine to straighten the rods and wires. After straightening, the straightness is 0.2mm / m.

[0092] Step 11: anneal the rods and wires at 600°C for 60 minutes.

[0093] Step 12: Use a centerless grinder to remove the surface oxide layer of the annealed rod wire, and use a plasma polisher to polish the wire. The surface roughness of the wire is 0.18 μm.

[0094] Table 2 shows the mechanical properties test results of Φ5.0 mm titanium-zirconium alloy rod and wire obtained in Example 2

[0095]

[0096] Example 3

[0097] The titanium-zirconium alloy rod and wire in this embodiment includes, by mass percentage, Zr: 16.20%, C: 0.005%, O: 0.191%, N: 0.005%, H: 0.002%, Fe: 0.019%, and the remainder is Ti.

[0098] The method for preparing the titanium-zirconium alloy rod and wire in this embodiment comprises:

[0099] Step 1: Use titanium sponge, zirconium sponge, ZrO 2 The powder is divided into titanium zirconium alloy components and smelted three times by vacuum self-consumption. The vacuum degree of the first smelting is 5×10 -3 Pa, working current 7.0kA, working voltage 30V; the vacuum degree of the second melting is 10 -1 Pa, working current 6.0kA, working voltage 30V; the third melting vacuum degree is 10 -1 Pa, working current 7.5kA, working voltage 30V; obtain Φ460mmTi-Zr alloy ingot.

[0100] Step 2: After keeping the ingot at 950°C for 2 hours, free forging is performed using a fast forging machine, and the deformation amount of each fire is controlled at 70% to obtain a Φ160mm billet.

[0101] Step 3: Keep the forging blank at 950°C for 1.5 hours and then quickly water cool it for quenching.

[0102] Step 4: After keeping the forging billet at 820° C. for 1.5 h, the forging billet is rolled using a Y-type three-roller continuous rolling mill, with the deformation amount of each pass controlled at 12% to obtain a Φ16 mm rolled bar.

[0103] Step 5: Keep the rolled strip at 780°C for 1 hour and then quickly water cool it for quenching.

[0104] Step 6: Use a cold rolling device to continuously cold roll the rolled strip, with a single-pass deformation of 8-10%. After the deformation reaches 40%-45%, intermediate annealing is performed at 650°C and 1h. After multiple cycles, a Φ12mm ultrafine grain rod blank is obtained.

[0105] Step 7: Keep the rod blank at 700°C for 0.5h and then air-cool it for recrystallization annealing heat treatment.

[0106] Step 8: Cut the rod into 200mm length, cut and cut the material, and perform equal-diameter angular extrusion. The processing temperature is 500℃, the turning angle is 120°, molybdenum disulfide is used as a lubricant, the processing speed is between 2mm / s, and the rod is rotated 90° clockwise after passing through the die each time, and the processing number is 8 times.

[0107] Step nine: cold-draw the equiaxed ultrafine grain rod blank using a drawing device, with a single-pass deformation of 10-13%. Lubricate with lubricating fluid, keep at 650°C for 1h for intermediate annealing, and then cold-draw again. After multiple cycles, Φ6mm rod wire is obtained.

[0108] Step 10: Cut the wire rods into 600mm lengths and use a slider straightening machine to straighten the wires. The straightness after straightening is 0.4mm / m.

[0109] Step 11: anneal the rods and wires at 550°C for 40 minutes.

[0110] Step 12: Use a centerless grinder to remove the surface oxide layer of the annealed rod and wire, and the surface roughness of the rod and wire is 0.56 μm.

[0111] Table 3 shows the mechanical properties test results of the Φ6.0 mm titanium-zirconium alloy wire obtained in Example 3

[0112]

[0113] Example 4

[0114] The titanium-zirconium alloy rod and wire in this embodiment includes, by mass percentage, Zr: 15.10%, C: 0.008%, O: 0.186%, N: 0.009%, H: 0.005%, Fe: 0.023%, and the remainder is Ti.

[0115] The method for preparing the titanium-zirconium alloy rod and wire in this embodiment comprises:

[0116] Step 1: Use titanium sponge, zirconium sponge, ZrO 2 The powder is divided into titanium zirconium alloy components and smelted three times by vacuum consumable method. The vacuum degree of the first smelting is 4×10-3 Pa, working current 6.0kA, working voltage 30V; the second melting vacuum degree is 10 -2 Pa, working current 6.0kA, working voltage 30V; the third melting vacuum degree is 10 -1 Pa, working current 8.0kA, working voltage 30V; obtain Φ280mmTi-Zr alloy ingot.

[0117] Step 2: After the ingot is kept at 900°C for 1.5 hours, it is free forged using a fast forging machine, with the deformation amount of each fire controlled at 70% to obtain a Φ120mm forging billet.

[0118] Step 3: Keep the forging blank at 950°C for 1.5 hours and then quickly water cool it for quenching.

[0119] Step 4: After keeping the forging billet at 800°C for 1.5 hours, the forging billet is rolled using a Y-type three-roller continuous rolling mill, with the deformation amount of each pass controlled at 13% to obtain a Φ18 mm rolled bar.

[0120] Step 5: Keep the rolled strip at 80°C for 1 hour and then quickly water cool it for quenching.

[0121] Step 6: Use a cold rolling device to continuously cold roll the rolled strip, with a single-pass deformation of 8-10%. After the deformation reaches 35%-45%, intermediate annealing is performed at 700°C and 1h. After multiple cycles, a Φ12mm ultrafine grain rod blank is obtained.

[0122] Step 7: Keep the rod blank at 680°C for 0.5h and then air-cool it for recrystallization annealing heat treatment.

[0123] Step 8: Cut the rod into 200mm length, cut and cut, and perform equal-diameter angular extrusion to obtain equiaxed ultrafine-grained alloy rods. The processing temperature is 500℃, the turning angle is 120°, molybdenum disulfide is used as a lubricant, the processing speed is between 2mm / s, and the rod rotates 90° clockwise after passing through the die each time, and the processing number is 7 times.

[0124] Step 9: Use a drawing device to cold draw the equiaxed ultrafine-grained alloy rod blank at room temperature, with a single-pass deformation of 10%. Lubricate with lubricating fluid, keep at 600°C for 1h for intermediate annealing, and then cold draw again. After multiple cycles, Φ7mm rod wire is obtained.

[0125] Step 10: Cut the rods into 600mm lengths and use a hyperbolic straightening machine to straighten the rods. The straightness after straightening is 0.5mm / m.

[0126] Step 11: anneal the rods and wires at 600°C for 40 minutes.

[0127] Step 12: Use a centerless grinder to remove the surface oxide layer of the annealed rod and wire, and the surface roughness of the rod and wire is 0.51 μm.

[0128] Table 4 shows the mechanical properties test results of the Φ7.0 mm titanium-zirconium alloy wire obtained in Example 4

[0129]

[0130] Comparative Example 1

[0131] The titanium-zirconium alloy rod and wire in this comparative example include, by mass percentage, Zr: 15.15%, C: 0.004%, O: 0.193%, N: 0.018%, H: 0.008%, Fe: 0.028%, and the balance is Ti.

[0132] The preparation method of the titanium-zirconium alloy rod and wire material in this comparative example comprises:

[0133] Step 1: Use titanium sponge, zirconium sponge, ZrO 2 The powder was divided into titanium-zirconium alloy components and smelted four times by vacuum self-consumption. The vacuum degree of the first smelting was 5×10 -3 Pa, working current 5.5kA, working voltage 30V; the vacuum degree of the second melting is 10 -2 Pa, working current 5.5kA, working voltage 30V; the third melting vacuum degree is 10 -1 Pa, working current 8.0kA, working voltage 30V; the fourth smelting vacuum degree is 10 -1 Pa, working current 7.5kA, working voltage 30V; obtain Φ260mmTi-Zr alloy ingot.

[0134] Step 2: After keeping the ingot at 900°C for 2 hours, free forging is performed using a fast forging machine, and the deformation amount of each fire is controlled at 60% to obtain a Φ120mm forging billet.

[0135] Step 3: Keep the forging blank at 900°C for 1.5 hours and air cool.

[0136] Step 4: After keeping the forging billet at 800° C. for 1.5 h, the forging billet is rolled using a Y-type three-roller continuous rolling mill, with the deformation amount of each pass controlled at 13% to obtain a Φ12 mm rolled bar.

[0137] Step 5: Keep the rolled strip at 780°C for 1 hour and then air cool it.

[0138] Step 6: Use a cold rolling device to continuously cold roll the rolled strip, with a single-pass deformation of 10%. After the deformation reaches 40%-45%, intermediate annealing is performed at 650°C and 1h. After multiple cycles, a Φ6mm ultrafine grain rod blank is obtained.

[0139] Step 7: Keep the rod blank at 700°C for 0.5h and then air-cool it for recrystallization annealing heat treatment.

[0140] Step 8: Cut the rod into 500mm length, cut and cut, and perform equal-diameter angular extrusion to obtain equiaxed ultrafine-grained alloy rods. The processing temperature is 400℃, the turning angle is 120°, molybdenum disulfide is used as a lubricant, the processing speed is between 5mm / s, and the rod rotates 90° clockwise after passing through the die each time, and the processing passes are 6 times.

[0141] Step nine, cold drawing the equiaxed ultrafine grain alloy rod blank at room temperature with a drawing device, a single-pass deformation of 11-13%, lubrication with lubricating fluid, intermediate annealing at 650°C for 1h, and then cold drawing again, after multiple cycles, Φ4mm rod wire is obtained.

[0142] Step 10: Cut the rods and wires into 1000mm lengths each, and use a slider straightening machine to straighten the rods and wires. After straightening, the straightness is 0.3mm / m.

[0143] Step 11: anneal the rods and wires at 600°C for 40 minutes.

[0144] Step 12: Use a centerless grinder to remove the surface oxide layer of the annealed rod and wire, and use wet polishing to polish the rod and wire surface to a roughness of 0.4 μm.

[0145] Table 5 shows the mechanical properties test results of the Φ4.0 mm titanium-zirconium alloy rod and wire obtained in Comparative Example 1

[0146]

[0147] Comparative Example 2

[0148] The titanium-zirconium alloy rod and wire in this comparative example include, by mass percentage, Zr: 15.15%, C: 0.004%, O: 0.193%, N: 0.018%, H: 0.008%, Fe: 0.028%, and the balance is Ti.

[0149] The preparation method of the titanium-zirconium alloy rod and wire in this comparative example comprises:

[0150] Step 1: Use titanium sponge, zirconium sponge, ZrO 2 The powder was divided into titanium-zirconium alloy components and smelted four times by vacuum self-consumption. The vacuum degree of the first smelting was 5×10 -3 Pa, working current 5.5kA, working voltage 30V; the vacuum degree of the second melting is 10 -2 Pa, working current 5.5kA, working voltage 30V; the third melting vacuum degree is 10-1 Pa, working current 8.0kA, working voltage 30V; the fourth smelting vacuum degree is 10 -1 Pa, working current 7.5kA, working voltage 30V; obtain Φ260mmTi-Zr alloy ingot.

[0151] Step 2: After keeping the ingot at 900°C for 2 hours, free forging is performed using a fast forging machine, and the deformation amount of each fire is controlled at 60% to obtain a Φ120mm forging billet.

[0152] Step 3: Keep the forging blank at 900°C for 1.5 hours and then quickly water cool it for quenching.

[0153] Step 4: After keeping the forging billet at 800° C. for 1.5 h, the forging billet is rolled using a Y-type three-roller continuous rolling mill, with the deformation amount of each pass controlled at 13% to obtain a Φ12 mm rolled bar.

[0154] Step 5: Keep the rolled strip at 780°C for 1 hour and then quickly water cool it for quenching.

[0155] Step 6: Use a drawing device to cold draw the equiaxed ultrafine-grained alloy rod blank at room temperature, with a single-pass deformation of 11-13%. Lubricate with lubricating fluid, keep at 650°C for 1h for intermediate annealing, and then cold draw again. After multiple cycles, Φ4mm rod wire is obtained.

[0156] Step 7: Cut the rods and wires into 1000mm lengths each, and use a slider straightening machine to straighten the rods and wires. After straightening, the straightness is 0.3mm / m.

[0157] Step 8: anneal the rods and wires at 600°C for 40 minutes.

[0158] Step 9: Use a centerless grinder to remove the surface oxide layer of the annealed rod and wire, and use wet polishing to polish the rod and wire surface to a roughness of 0.4 μm.

[0159] Table 6 is the mechanical properties test results of the Φ4.0 mm titanium-zirconium alloy rod and wire obtained in Comparative Example 2

[0160]

[0161] Comparative Example 3

[0162] The titanium-zirconium alloy rod and wire in this comparative example include, by mass percentage, Zr: 15.15%, C: 0.004%, O: 0.193%, N: 0.018%, H: 0.008%, Fe: 0.028%, and the balance is Ti.

[0163] The preparation method of the titanium-zirconium alloy rod and wire material in this comparative example comprises:

[0164] Step 1: Use titanium sponge, zirconium sponge, ZrO 2 The powder was divided into titanium-zirconium alloy components and smelted four times by vacuum self-consumption. The vacuum degree of the first smelting was 5×10 -3 Pa, working current 5.5kA, working voltage 30V; the vacuum degree of the second melting is 10 -2 Pa, working current 5.5kA, working voltage 30V; the third melting vacuum degree is 10 -1 Pa, working current 8.0kA, working voltage 30V; the fourth smelting vacuum degree is 10 -1 Pa, working current 7.5kA, working voltage 30V; obtain Φ260mmTi-Zr alloy ingot.

[0165] Step 2: After keeping the ingot at 900°C for 2 hours, free forging is performed using a fast forging machine, and the deformation amount of each fire is controlled at 60% to obtain a Φ120mm forging billet.

[0166] Step 3: Keep the forging blank at 900°C for 1.5 hours and air cool.

[0167] Step 4: After keeping the forging billet at 800° C. for 1.5 h, the forging billet is rolled using a Y-type three-roller continuous rolling mill, with the deformation amount of each pass controlled at 13% to obtain a Φ12 mm rolled bar.

[0168] Step 5: Keep the rolled strip at 780°C for 1 hour and then air cool it.

[0169] Step 6: Use a drawing device to cold draw the equiaxed ultrafine-grained alloy rod blank at room temperature, with a single-pass deformation of 11-13%. Lubricate with lubricating fluid, keep at 650°C for 1h for intermediate annealing, and then cold draw again. After multiple cycles, Φ4mm rod wire is obtained.

[0170] Step 7: Cut the rods and wires into 1000mm lengths each, and use a slider straightening machine to straighten the rods and wires. After straightening, the straightness is 0.3mm / m.

[0171] Step 8: anneal the rods and wires at 600°C for 40 minutes.

[0172] Step 9: Use a centerless grinder to remove the surface oxide layer of the annealed rod and wire, and use wet polishing to polish the rod and wire surface to a roughness of 0.4 μm.

[0173] Table 7 is the mechanical properties test results of the Φ4.0 mm titanium-zirconium alloy rod and wire obtained in Comparative Example 3

[0174]

[0175] Compared with Example 1, Comparative Example 1 lacks quenching process, and step three and step five adopt air cooling; Comparative Example 2 lacks cold rolling and large plastic deformation process compared with Example 1; Comparative Example 3 lacks quenching, cold rolling and large plastic deformation process compared with Example 1. Compared with Examples 1-4, the tensile strength, yield strength, elongation after fracture and cross-sectional shrinkage of titanium zirconium alloy rods and wires in Comparative Examples 1-3 are significantly reduced. Examples 1-4 are equiaxed ultrafine-grained titanium zirconium alloy rods and wires prepared by the preparation method of medical equiaxed ultrafine-grained titanium zirconium alloy rods and wires provided by the present invention. The titanium zirconium alloy rods and wires in Examples 1-4 have high tensile strength, yield strength, elongation after fracture and cross-sectional shrinkage. The present invention introduces high-density defects in the material by severe plastic deformation and combines quenching heat treatment to regulate the microstructure of the alloy, so as to realize the preparation of equiaxed ultrafine-grained titanium zirconium alloy rods and wires with high-strength plasticity and good fracture toughness, and can obtain high strength and high fatigue strength to meet the demand for raw materials of dental medical equipment.

[0176] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire, characterized in that: include: S1. Mix titanium sponge, zirconium sponge and zirconium dioxide according to a preset ratio and melt them into ingots; S2. After the ingot is kept at 850°C-1000°C, it is forged to obtain a forged billet; S3. The forging blank is subjected to a first quenching treatment; S4. The forging blank is kept at 770°C-840°C and then rolled to obtain a rolled strip; S5. The rolled strip is subjected to a second quenching treatment; S6. rolling the rolled strip at room temperature to obtain an ultrafine grained rod blank; S7. Recrystallization annealing treatment is performed on the ultrafine grained rod blank; S8. The ultrafine crystal rod blank is subjected to severe plastic deformation processing to obtain an equiaxed ultrafine crystal rod blank; S9. Drawing and reducing the equiaxed ultrafine grained rod blank at room temperature to obtain a rod wire; S10. Straightening the rod wire; S11. Annealing the rod wire; S12. Surface treatment is performed on the rods and wires to obtain qualified rods and wires.

2. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: In step S1, vacuum self-consumption is used for 3-4 times of melting, and the vacuum degree is 10 -1 P-10 -3 Pa, a working current of 1kA-10kA, and a working voltage of 10V-50V to obtain the ingot.

3. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: In step S2, the ingot is kept at 850°C-1000°C for 1h-5h, air-cooled, and free forged by a fast forging machine, with the deformation amount of each fire being not less than 50%, to obtain the forging blank.

4. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: In step S4, the forging blank is kept at 770° C.-840° C. for 1 h-3 h, and then rolled by a horizontal rolling mill, with a single-pass deformation rate of less than 15%, to obtain the rolled strip.

5. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: In step S6, a cold rolling mill is used to roll the strip at room temperature, and the deformation of a single pass is less than 15% and the total deformation is greater than 50%.

6. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: The recrystallization annealing in step S7 includes keeping the ultrafine crystal rod blank at 600° C.-700° C. for 0.5 h-3 h and then air cooling it.

7. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: The severe plastic deformation in S8 includes: performing equal-diameter angular extrusion on the ultrafine crystal rod blank through a die, using molybdenum disulfide as a lubricant, the equal-diameter angular extrusion processing speed is 1mm / s-10mm / s, the processing temperature is 400℃-500℃, and the processing number is 4-8 times.

8. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: In S9, a roller mill drawing device is used to perform multiple drawing passes, and the deformation amount of a single pass is between 10% and 15%. Subsequently, stress relief annealing is performed, and the rod wire is obtained after multiple drawing passes.

9. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: In S11, an annealing furnace is used to anneal the rods and wires at a temperature of 450° C. to 650° C. for a time of 20 min to 90 min.

10. The method for preparing medical equiaxed ultrafine-grained titanium-zirconium alloy rod and wire according to claim 1, characterized in that: In S12, a centerless grinder, a pickling polishing or a plasma polishing surface treatment equipment is used to perform surface treatment on the rod and wire to remove oxide scale on the surface of the rod and wire. The surface roughness of the qualified rod and wire is less than or equal to 0.8 μm.

Citation Information

Patent Citations

  • Si-containing high-strength low-modulus Beta-type titanium alloy and preparation method and application thereof

    CN107034383A

  • Low-temperature superplastic titanium alloy plate, low-temperature superplastic titanium alloy bar and preparation method

    CN112322930A

  • Equiaxed nanocrystalline Ti-Zr-Ni alloy with high thermal stability and preparation method thereof

    CN112342435A

  • Processing method for preparing TB8 titanium alloy sheet in short process

    CN114101556A

  • Method for preparing nano lamellar copper-chromium-zirconium alloy through composite shaping deformation

    CN115305420A

Cited By

  • Ti15Mo alloy material post-treatment method and Ti15Mo alloy material

    CN120479967A

  • Titanium alloy shackle and machining method thereof

    CN120644927A

  • Method for preparing titanium-zirconium alloy wire in short process, titanium-zirconium alloy wire and application

    CN121156074A

  • Regulation and control method for improving strength and plasticity balance of titanium alloy

    CN121407004A

  • Preparation method of carbon-niobium composite ultrahigh-strength titanium alloy pipe

    CN122142125A